Cyclophilin D Is Involved in the Regulation of Autophagy and Affects the Lifespan of P. anserina in Response to Mitochondrial Oxidative Stress - Kramer, Piet; Jung, Alexander T.; Hamann, Andrea; Osiewacz, Heinz D. (Frontiers in Genetics, 2016)
The mitochondrial permeability transition pore plays a key role in programmed cell death and the induction of autophagy. Opening of the mPTP is regulated by the mitochondrial peptidyl prolyl-cis,trans-isomerase cyclophilin D (CYPD). Previously it was shown in the aging model organism Podospora anserina that PaCYPD abundance increases during aging and that PaCypD overexpressors are characterized by accelerated aging. Here, we describe a role of PaCYPD in the regulation of autophagy. We found that the accelerated aging phenotype observed in a strain overexpressing PaCypD is not metacaspase-dependent but is accompanied by an increase of general autophagy and mitophagy, the selected autophagic degradation of mitochondria. It thus is linked to what has been defined as ‘autophagic cell death’ or ‘type II’ PCD. Moreover, we found that the previously demonstrated age-related induction of autophagy in wild-type aging depends on the presence of PaCYPD. Deletion of PaCypD leads to a decrease in autophagy in later stages of age and under paraquat-mediated oxidative stress. Finally, we report that PaCYPD is also required for mitohormesis, the beneficial effect of mild mitochondrial stress. Thus, PaCYPD plays a key role in the context-dependent regulation of pathways leading to pro-survival and pro-death effects of autophagy.